The Application of Accelerated Learning Method Assisted by a Media Playing Card to Improve Learning Outcomes and Interesting Learning in Science Students of SMP Negeri 1 Barru - Nur Amaliah Akhmad; Syahruni Karim (Universitas Muhammadiyah Makassar, 2019)
The purpose of this study to see an increase in science learning outcomes and student learning interest after being taught using the accelerated learning method assisted by media playing quartet cards. This type of research is quantitative with data collection using Quasi-experiments with models Pretest-Postest Nonequivalent-Group Design. The population in this study is the eighth-grade students of state junior high school Negeri 1 Barru academic year 2018/2019. Sampling was done by purposive sampling with consideration of looking at 2 classes with the lowest score of daily test results in the previous material. Students in both classes almost have relatively similar test results. Data collection is taken through direct observation, learning outcomes tests, questionnaires, teacher interviews. After data collection was carried out using the pretest and posttest tests, data was obtained that there were differences in the increase in learning outcomes between the 2 classes. And the interest in learning in these two classes has a fairly good score in line with the good response to treatment that was tested on the experimental class.Keywords: Accelerated Learning; Quarted Card Media, Science LearningTujuan dari penelitian ini untuk melihat peningkatan hasil belajar IPA dan minat belajar siswa setelah diajarkan menggunakan metode Accelerated learning berbantuan media bermain kartu kuartet. Jenis penelitian ini adalah kuantitatif dengan pengambilan data menggunakan Quasi eksperimen dengan model Pretest- Postest Nonequivalent-Group Design. Populasi pada penelitian ini adalah siswa kelas VIII SMP Negeri 1 Barru tahun ajaran 2018/2019. Pengambilan sampel secara purposive sampling dengan pertimbangan melihat 2 kelas dengan nilai terendah hasil ulangan harian dimateri sebelumnya. Siswa di kedua kelas hampir memiliki nilai hasil ujian yang relatif sama Pengumpulan data yang diambil melalui observasi langsung, tes hasil belajar, angket, wawancara guru. Setelah diakukan pengambilan data dengan tes pretest dan postest maka diperoleh data bahwa terdapat perbedaan peningkatan hasil belajar antara 2 kelas. Serta minat belajar di dua kelas ini memiliki skor yang cukup baik selaras dengan respon yang baik terhadap treatment yang diuji cobakan pada kelas eksperimen.Kata kunci: Accelerated Learning; Media Kartu Kuartet; Pembelajaran IPA